DFD Schema: A versatile approach for XML based representation of DFD - Shah, T.R (International Journal of Computer Sciences and Engineering, 2018)
The Requirement Engineering phase begins with inception and elicitation of functional, non functional requirements and concludes iteratively with modeling and specification. Requirement Engineering demands the coarse level of requirement specification by primary objectives, design constraints and appropriate artifacts of a system. In system development life cycle (SDLC), a system model is analysed and developed using Data Flow Diagram (DFD). DFD is graphical diagram for analyzing, specifying, creating and visualizing the model of a system. The formal requirement analysis and specification method like DFD experiences the problem of ambiguity with different notation and complex graphical presentation. This paper introduces DFD Schema; an XML based versatile specification approach for the structural representation of DFD of a system. Its definition was motivated by lack of available structured and open formats that describe data flow of system with its artifacts. This schema can be used in an interoperable way to transfer data flow requirements.